ANNE J. GILLILAND, Conceptualizing 21st-Century Archives - Shepherd, Elizabeth (Archivaria, 2015)
Conceptualizing 21st-Century Archives. ANNE J. GILLILAND. Chicago: Society of American Archivists, 2014. xii, 322 pp. ISBN 978-1-931666-68-8.